AB0409 APL PREVALENCE IN WOMEN WITH LATE PREGNANCY COMPLICATION AND LOW-RISK FOR CHROMOSOMAL ABNORMALITIES. (2nd June 2020) - Foddai, S. G.; Radin, M.; Cecchi, I.; Rubini, E.; Gaito, S.; Marozio, L.; Manetta, T.; Mengozzi, G.; Sciascia, S.; Roccatello, D.
Abstract : Background: Current guidelines help defining correct pregnancy standard of care for patients with antiphospholipid syndrome (APS) and antiphospholipid antibodies (aPL) carriers, but little is known about the significance of aPL detection during pregnancy and their association with clinical manifestations of the syndrome [1]. Objectives: Investigate the presence of aPL antibodies in a cohort of women who experienced late onset pregnancy complications (LO-PC) and low-risk for chromosomal abnormalities. Methods: We retrospectively collected clinical, demographic and laboratory data of women ever pregnant from August 2017 to August 2018, who attended the S. Anna University Clinic (Turin, Italy). Inclusion criteria were LO-PC, negative triple test and absence of US foetal abnormalities. 100 patients have been recruited and, as control, 100 women matched for age with normal pregnancy. aPL testing was performed on serum samples derived from pregnancy screening test collected between 15 and 18w of gestation. Criteria and "extra criteria" aPL were tested. Results: Number of aPL positivity (aPL+) was statistically different between patients and controls: 31 aPL+ vs 10 aPL+, respectively (p-value <0.001; p<0.01)(Graph 1). Patients' population had a significant higher percentage of single aPL+ (p-value < 0.001; p < .05) and, among single isotypes, of ACA IgG (p-value 0.017; p < 0.05) and aPS/PT IgM (p-value 0.0378; p <0.05). Moreover, patients' population had a significant higher aPL titre of ACA IgG and aPS/PT IgM (p-value <0.0001, p < 0.05; p-value 0.0061, p < 0.05). When comparing aPL+ and aPL negative (aPL-) patients for median age at conception, mode of delivery, foetal outcomes, maternal and foetal pregnancy complication, maternal and foetal post-partum complication and histology findings (see Table 1 ), we found that aPL+ patient had a significant higher presence of IUGR (P<0.01) and pre-term birth (34-36 + 6w; p<0.012). When we granulated data for presence/absence of an underlying disease (UD), we found that 29 women had an UD, mostly arterial hypertension and hypothyroidism (59%, not shown), while 71 were healthy (H). When comparing aPL+/aPL- in UD patients' subgroub, we found no difference; instead, when comparing aPL+/aPL- in H patients' subgroup we found that aPL+ had a significant higher percentage of pre-term birth (34-36w; p<0. 001). aPS/PT IgM isotype, alone, allowed the detection 17 patients who tested negative for aPL criteria (Graph 1). Conclusion: Our results, even if preliminary, suggest a direct correlation between aPL positivity and risk of development of LO-PM. In conclusion, testing for both criteria and "extra criteria" aPL in women with previous LO-PM could improve the diagnostic accuracy identifying women at higher risk in case of future pregnancy. References: [1]Tektonidou, EULAR recommendations for the management of APS in adults. Ann Rheum Dis (2019) Disclosure of Interests: None declared